ПЕЙЗАЖЛЫҚ СҮЎРЕТЛЕЎДИҢ ЭСТЕТИКАЛЫҚ КҮШИ - Сейтниязов, Т. (FAN va JAMIYAT, 2025)
The article discusses the issues of landscape depiction in works of art. In particular, the role of the author’s artistic skill and style is emphasized.